The Influence of Brand Reputation, Quality of Information, and Word of Mouth on Brand Trust to Build Brand Loyalty in Environmentally Friendly Body Care Products - Salwa Salsabila, Julia; Usep Suhud; Dewi Agustin Pratama Sari (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2024)
The purpose of this research is to determine the influence of brand reputation, quality of information, and word of mouth on brand reputation in environmentally friendly body care products. This quantitative research method collects data through questionnaires. A total of 254 respondents were sampled using purposive sampling technique. The objects taken in this research were respondents who had purchased environmentally friendly body care products at least 3 times in DKI Jakarta and were at least 18 years old. This research uses SPSS version 26 software and SEM (Structural Equation Model) from AMOS software to carry out the analysis and processing of research data. The results obtained in this research show that brand reputation, quality of information, and word of mouth have a positive and significant effect on brand trust. Apart from that, brand reputation and brand trust have a positive and significant effect on brand loyalty.